Kinetic study on Fermentation of xylose for The Xylitol Production - Efri Mardawati; Andi Trirakhmadi; MTAP Kresnowati; Tjandra Setiadi (Universitas Padjadjaran, 2017)
Xylitol is a natural sugar that has the sweetness level similar to sucrose, but has lower calorie. It is an important sugar alternate for diabetics people. Reduction of xylose is a normally method to produce the xylitol. It Conducted via chemical hydrogenation of xylose at high pressures and temperatures by reacting pure xylose with hydrogen gas using a metal catalyst. This process requires pure xylose as the raw material. Alternatively, the reduction process can be carried out via fermentation. This process does not require high purity of xylose as the raw material, and thus the oil palm empty fruit bunch (EFB) hydrolysate, without any prior pretreatment, can be used. In order to scale up the xylitol production via fermentation, kinetic study of xylitol fermentation including growth and xylitol formation kinetic using the synthetic xylose as substrate will be required. Data used in the kinetic model development were obtained from series of batch fermentations of Debaryomycess hansenii ITB CCR85 varying the initial xylose and glucose concentrations. Yeast growth could be sufficiently modeled using the Monod kinetics, whereas xylitol production could be reasonably well modelled by Luedeking Piret kinetics.